Refractive and corneal responses of young myopic children to short-term orthokeratology treatment with different compression factors. Issue 1 (February 2020) - Wan, Kin; Lau, Jason Ki-kit; Cheung, Sin Wan; Cho, Pauline
Highlights: Increasing the compression factor of orthokeratology lenses by 1.00 D leads to faster refractive correction. Increased compression did not affect the ortho-k lens fitting. External ocular health was not compromised by increased compression factor. No significant differences in the corneal biometrics between eyes fitted with different compression factors (0.75 and 1.75 D). Abstract: Purpose: To evaluate changes in refractive and corneal responses in myopic children wearing orthokeratology (ortho-k) lenses with conventional compression factor (CCF, 0.75 D) and increased compression factor (ICF, 1.75 D). Methods: This was a double-blind self-controlled study. Subjects were randomly fitted with CCF in one eye and ICF in the fellow eye. Weekly monitoring of refraction, visual acuity (VA), external ocular health, and corneal responses were performed over one month of lens wear and after discontinuation of lens wear until stabilization was achieved. Results: Twenty-five subjects, aged 9.4 ± 1.0 years, completed one-month lens wear, of whom 23 completed the washout period. The first fit success rates for CCF and ICF were 93% and 96%, respectively. Myopia, unaided VA, central corneal thickness, anterior corneal curvatures (K), apical power (AP), and corneal resistance factor (CRF) all changed significantly during the study period ( P  <  0.003). Between-eye difference was significant only for myopia reduction ( P  =  0.001). About 4% and 8% of ICF and CCF eyes were under-corrected. The attempted target was achieved in about 80% of CCF and 60% of ICF eyes at week 4. At the end of the washout period (3 weeks), myopia, K, and AP were significantly different compared to baseline ( P  <  0.001). Conclusion: Increasing the compression factor did not affect the first fit success rate and external ocular health, but did allow faster correction of refractive error within one month of lens wear. Further investigation is warranted to investigate the long-term effects of ICF on myopia control compared to CCF.